2020
DOI: 10.1021/jacs.9b10510
|View full text |Cite
|
Sign up to set email alerts
|

Molecularly Engineering Triptolide with Aptamers for High Specificity and Cytotoxicity for Triple-Negative Breast Cancer

Abstract: Triple-negative breast cancer (TNBC) lacks three important receptors, ER, PR, and HER2. It is more aggressive and more likely to relapse after treatment, thus has been identified as one of the most malignant breast cancer types. The development of efficient targeted TNBC therapy is an important research topic in TNBC treatment. We report the development of a new aptamer–drug conjugate (ApDC), AS1411–triptolide conjugate (ATC), as targeted therapy for the treatment of TNBC with high efficacy. The conjugate poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
92
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(92 citation statements)
references
References 35 publications
(49 reference statements)
0
92
0
Order By: Relevance
“…Various aptamers have been developed for therapy in TNBC; for example, the aptamer 5TR1 pursues the molecular target MUC1 which is a tumor protein in MDA-MB-231, the researchers have conjugated 5TR1 to Doxorubicin to make it more specific and avoid the known side effects such as cardiotoxicity [147]. He et al have reported aptamer-drug conjugate (ApDC), AS1411-triptolide conjugate (ATC) for TNBC therapeutics with higher efficacies [148]. Nanomedicine is advancing rapidly, and now researchers have focused on combining all the technologies mentioned above (siRNA, miRNA, aptamers) by loading them into nanoparticles that pursue the CD-44 receptor characteristic of TNBC pluripotent cells [149].…”
Section: Aptamersmentioning
confidence: 99%
“…Various aptamers have been developed for therapy in TNBC; for example, the aptamer 5TR1 pursues the molecular target MUC1 which is a tumor protein in MDA-MB-231, the researchers have conjugated 5TR1 to Doxorubicin to make it more specific and avoid the known side effects such as cardiotoxicity [147]. He et al have reported aptamer-drug conjugate (ApDC), AS1411-triptolide conjugate (ATC) for TNBC therapeutics with higher efficacies [148]. Nanomedicine is advancing rapidly, and now researchers have focused on combining all the technologies mentioned above (siRNA, miRNA, aptamers) by loading them into nanoparticles that pursue the CD-44 receptor characteristic of TNBC pluripotent cells [149].…”
Section: Aptamersmentioning
confidence: 99%
“…Aptamer-mediated targeting assay in vitro AS1411 speci cally targets nucleolin, which is overexpressed by many tumors [30][31][32] . Therefore, we investigated the internalization of AS1411-CS/rGO/Ag + -DNA into HepG2 cells, which overexpress nucleolin.…”
Section: Synthesis Of a Bioreactor Carrying The Ag + Prodrugmentioning
confidence: 99%
“…44,45 Generally, most breast cancer diagnoses are related to luminal tumors, 20% relates to those that overexpress HER2, while only 15% refers to TNBC subtype. 44 Even though the percentage of TNBC tumors among all breast cancer cases is relatively low, they represent the most aggressive phenotype 46 with the highest rate of metastasis to other healthy organs, high proliferative index, high recurrence rate (o5 years), 47 and a worse prognosis. 48 Nowadays, the most common treatments for TNBC patients include surgery, radiotherapy and chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…48 Nowadays, the most common treatments for TNBC patients include surgery, radiotherapy and chemotherapy. 46,49 During the last few years, CPNs have been reported as promising materials in photodynamic therapy of breast cancers. [49][50][51] In this contribution, we performed in vitro studies in order to evaluate the cytotoxicity effects of the T2fQf and T2fQ2f (chemical structures on Fig.…”
Section: Introductionmentioning
confidence: 99%